Analisa Sistem Pengendalian Manajemen pada Penjualan Usaha Daster Dasby’D - Sheila Permatasari Eliso; Rizka Maulida Arinanda; Fitri Nur Aini; Amin Sadiqin (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
The purpose of this research is to be able to know and understand what the application of the sales management control system is like in Dasby'D's business. Dasby'D is a business trading daster clothes and women's pajamas that have a business process, namely buying daster in large quantities/wholesale to convection at prices that can be reached by all levels of society and has good quality, which will later be marketed through outlets and also digital markets. In its operational activities, Dasby'D prepares an operating budget that aims to provide information on the expected performance of each business owner. The Management Control System in a business has the task of determining and ensuring the company's operating budget can reach sales and profit. The data analysis technique used is to use deductive analysis methods and also descriptive analysis methods. Research that has been carried out shows that, Dasby'D's efforts in achieving success in controlling the purchase of merchandise and the use of finance in business operations. Profit acquisition is one of the performance standards in companies getting a return of around 20% of revenue. This informs that the company's operating performance is a standard of performance achievement for a business that has experienced growth in a good and positive direction.